Study of the prescription pattern of anti-depressants in a tertiary care hospital: a prospective observational study - Kulkarni, Vishal A.; Baig, Mirza S.; Deshpande, Prasad (International Journal of Research in Medical Sciences, 2023)
Background: One of the most important public health priorities are psychiatric disorders. Prescribing medications play a crucial role in providing good health care. Therefore, there is a need to understand prescription patterns at regular intervals. Methods: This was a prospective, cross-sectional, observational study conducted at the psychiatry department OPD of Government Medical College, Aurangabad (Maharashtra, India) from January 2021 to June 2022. Records of prescriptions were collected from the hospital management information system. Results: N=417 prescriptions were analysed. The male: female ratio was 1.25. Among total prescriptions analysed, selective serotonin reuptake inhibitors (SSRIs) were the most prescribed drug class (32.18%) followed by benzodiazepines (25.19%) and atypical antipsychotics (19.97%). Drugs prescribed as fixed dose combinations (FDC) were 2.10%. Most of the patients received polytherapy in which most patients constituted of two drug therapy (46.28%) and 34.53% of patients received monotherapy. In the patients managed by monotherapy, SSRIs were the most prescribed (29.16%), followed by atypical anti-psychotics (26.38%) and benzodiazepines (24.30%). Prescriptions with generic names were 93.12%. The average number of drugs per encounter was 1.88. Drugs prescribed from the essential drugs list (India) were 41.66%. Drugs prescribed from the essential medicines list (WHO) were 47%. The total number of prescriptions with injections 0.23%. Conclusions: Prescribing patterns were according to the WHO-DUS parameters. Most patients were prescribed generic medicines. SSRIs, benzodiazepines and tricyclic antidepressants were the most prescribed drug class.